Determinant of Malaysian passengers’ acceptance towards electronic ticketing: a study on Malaysia Airline System (MAS) / Siti Hasnida Hadzir - Hadzir, Siti Hasnida (2012)
The purpose of this research is to illustrate the key factors affecting the Malaysian passengers’ acceptance towards electronic ticketing provided by Malaysia Airline System (MAS). The primary data had been collected through 100 valid questionnaire surveys from target respondents who are students and working adults between 18 and 55 years old in Airport Subang. In this study, the researcher collects the information from the questionnaire, website and the secondary data such as journals, articles and text book. The collected data discussed, compared and then finally used to draw general conclusions. After all data has been gathered, it will be interpreted to make it sense for supporting the problem identified. The findings of the study were useful for Malaysia Airline industry as a reference in identifying consumers’ perception and attitude to further improve the e-ticketing system. This paper would also contribute to the companies and to the public on future trend and development of e-ticketing.